Serum 25-hydroxyvitamin d level and influenza vaccine immunogenicity in children and adolescents. - Michelle Science; Jonathon L Maguire; Margaret L Russell; Marek Smieja; Stephen D Walter; Mark Loeb (PLoS ONE, 2014)
Vaccination is an important strategy in the prevention of influenza, but immunologic response to vaccination can vary widely. Recent studies have shown an association between serum 25-hydroxyvitamin D (25[OH]D) levels and immune function. The purpose of this study was to determine if serum 25(OH)D level correlates with influenza vaccine immunogenicity in children and adolescents.We conducted a prospective cohort study of children age 3 to 15 years of age vaccinated with trivalent influenza vaccine (A/Brisbane/59/2007[H1N1]-like virus, A/Brisbane/10/2007 [H3N2]-like virus and B/Florida/4/2006-like virus) in Hutterite communities in Alberta, Saskatchewan and Manitoba. Serum 25(OH)D levels were measured at baseline and immunogenicity was assessed using hemagluttination inhibition (HAI) titers done at baseline and 3-5 weeks post vaccination. Logistic regression was used to assess the relationship between serum 25(OH)D level as both a continuous and dichotomous variable and seroprotection, seroconversion, fold increase in geometric mean titer (GMT) and post vaccination titer.A total of 391 children and adolescents were included in the study and 221 (57% had post-vaccination HAI titers. The median serum 25(OH)D level was 61.0 nmol/L (Interquartile range [IQR] 50.0, 71.0). No relationship was found between serum 25(OH)D level and seroprotection (post-vaccination titer ≥ 40 and ≥ 320) or seroconversion (post-vaccination titer ≥ 40 for participants with pre-vaccine titer <10 or four-fold rise in post-vaccination titer for those with a pre-vaccine titer ≥ 10).Serum 25(OH)D level was not associated with influenza vaccine immunogenicity in otherwise healthy children and adolescents. Other strategies to enhance influenza vaccine response should continue to be evaluated in this population. The role of serum 25(OH)D level in vaccine responsiveness in other populations, especially those hyporesponsive to influenza vaccination, requires further study.